(untitled) (Texas Journal of Philology, Culture and History, 2026)
In the field of Mathematics, English for Specific Purposes (ESP) serves as the primary vehicle for global academic discourse. While lexical mastery of mathematical terminology is vital, the role of grammar as a foundational tool for precision is often undervalued. This article explores the symbiotic relationship between grammatical accuracy and logical rigor in mathematical English. It argues that specific grammatical structures—such as the passive voice, conditional clauses, and modal verbs—are not merely stylistic choices but essential instruments for defining theorems, describing algorithms, and maintaining objectivity. The study proposes a functional approach to teaching grammar within Mathematics ESP to bridge the gap between linguistic form and mathematical meaning.